2007
DOI: 10.24252/lp.2007v10n2a4
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Synectics Dipadu Mind Maps Terhadap Kemampuan Berpikir Kreatif, Sikap Kreatif, Dan Penguasaan Materi Biologi

Abstract: One of the important tasks in teaching is assisting students to think. Synectics Model matched with Mind Maps are viewed necessary to be applied in the instruction in order to achieve the target.The research is an experiment research with pre-test posttest control group design. The results of analyses indicate that: (1) there is significance difference with the mean score of creative think ability, creative attitude, and mastery of biology materials due to difference of instruction model used, (2) there is no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
9
Order By: Relevance
“…STAD with the Mind Mapping technique has previously been applied by Mustami (2007) in his thesis which found that the synectics learning model combined with STAD's mind maps and cooperative learning had a positive effect on the mastery of biology material in Makassar city junior high school students. The results obtained in this study show different results compared to previous studies.…”
Section: Integration Of Stad Withmentioning
confidence: 99%
“…STAD with the Mind Mapping technique has previously been applied by Mustami (2007) in his thesis which found that the synectics learning model combined with STAD's mind maps and cooperative learning had a positive effect on the mastery of biology material in Makassar city junior high school students. The results obtained in this study show different results compared to previous studies.…”
Section: Integration Of Stad Withmentioning
confidence: 99%
“…Hasil tes keterampilan berpikir kreatif siswa juga dianalisis secara deskriptif kuantitatif dan deskriptif kualitatif, yaitu dengan analisis N-Gain dan analisis sensitivitas butir soal. Selain mengunakan tes kreativitas verbal dan tes kreativitas produk, pengukuran keterampilan berpikir kreatif siswa dilakukan menggunakan skala sikap kreatif yang dikembangkan oleh Mustami (2007).…”
Section: Extended Abstracunclassified
“…Menentukan patokan penilaian sendiri dan penentuan apakah suatu pertanyaan benar, suatu rencana sehat, atau suatu tindakan bijaksana, mampu mengambil keputusan terhadap situasi yang terbuka, serta tidak hanya mencetuskan gagasan tetapi juga melaksanakannya. Mustami (2007). Skala sikap kreatif tidak diuji validitasnya karena mengacu pada skala sikap kreatif yang dikembangkan oleh Mustami (2007).…”
Section: Keterampilan Menilaiunclassified
See 1 more Smart Citation
“…Penelitian yang telah dilakukan selama ini hanya mengungkapkan ketidak sesuaian antara tingkat pencapaian penguasaan konsep dengan pola berpikir siswa. Tetapi, pola berpikir siswa yang dideteksi selama ini masih menggunakan indikator berpikir deduktif-induktif [10] , pola berpikir logis-kreatif [11] , dan pola kemampuan berpikir kreatif-kritis-pemecahan masalahpengambilan keputusan [12,13] . Oleh karena itu, diperlukan penyelidikan pola berpikir siswa dengan menggunakan indikator Bloom karena mayoritas soal yang disusun guru di berbagai sekolah masih menggunakan indikator keterampilan berpikir tingkat tinggi tersebut.…”
Section: Pendahuluanunclassified